The effect of triangularity on fluctuations in a tokamak plasma. (21st December 2017) - Fontana, M.; Porte, L.; Coda, S.; Sauter, O.
Abstract: The effects of plasma shaping, in particular triangularity ( δ ), on temperature fluctuations in the tokamak à configuration variable have been studied using the correlation electron cyclotron emission system. It has been found that, in ohmic discharges with comparable density profiles, the relative fluctuation level measured at the edge is significantly reduced in plasmas with negative triangularity with respect to positive triangularity ones. Additionally, the critical temperature gradients for the onset of turbulence are observed to increase in the negative triangularity plasmas. An estimation of the correlation length of the fluctuating structure shows smaller structure size in the negative triangularity cases, which are known to be associated with improved confinement. Together, these observations suggest that changing triangularity from positive to negative strongly influences the nature of the turbulent fluctuations excited in the plasma.